Septo-Optic Dysplasia and Cortical Malformations - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Three children with septo-optic dysplasia (SOD) and an associated malformation of cortical organization are reported from McGill University and the Montreal Children's Hospital, Quebec, Canada.